2017
DOI: 10.4049/jimmunol.1601815
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Human CCR6+ Regulatory T Cells with Superior Suppressive Activity in Oral Cancer

Abstract: Human oral squamous cell carcinoma (OSCC) constitutes an inflammatory microenvironment enriched with chemokines such as CCL20, which promote cancer cell invasion and tumor progression. We found that in OSCC there is a correlation between the expression of and mRNA. Therefore, we hypothesized that OSCC may favor the recruitment and retention of regulatory T (Treg) cells that express the CCL20 receptor, CCR6. Interestingly, most (∼60%) peripheral blood Treg cells express CCR6, and CCR6 Treg cells exhibit an acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 61 publications
2
33
0
Order By: Relevance
“…CCL20 attracts cells expressing the CCR6 receptor, such as dendritic cells and memory and effector T cells. Several studies have found that CCL20 is a chief attractant of Treg cells, a distinct lineage of CD4+ T cells that suppresses antitumor immune responses [53][54][55]. Interestingly, tumor cells may also express CCR6, and accordingly, CCL20 has been associated with migration and metastases of cancer cells [56].…”
Section: Variablementioning
confidence: 99%
“…CCL20 attracts cells expressing the CCR6 receptor, such as dendritic cells and memory and effector T cells. Several studies have found that CCL20 is a chief attractant of Treg cells, a distinct lineage of CD4+ T cells that suppresses antitumor immune responses [53][54][55]. Interestingly, tumor cells may also express CCR6, and accordingly, CCL20 has been associated with migration and metastases of cancer cells [56].…”
Section: Variablementioning
confidence: 99%
“…Therefore, for the survival of Tregs, an outer supply of IL-2 is essential [ 52 ]. In tumor tissues, many Tregs develop into effector Tregs which express CTLA-4, PD-1 or CCR6 at higher levels, and engage in the disruption of host immune systems including those in OSCC patients [ 53 - 55 ]. The elevated Foxp3 protein expression is a predictive factor for OSCC progression [ 56 ].…”
Section: Regulatory T Cells In the Immune Suppressive Strategies In Cmentioning
confidence: 99%
“…Moreover, in the meta-analysis of Liu et al (48) on patients with cervical carcinoma, CDH1 promoter methylation was signi cantly higher in cancer than in cervical intraepithelial neoplasia lesions and healthy cervical tissues.The rst fteen genes that were signi cantly hypomethylated on different sites across the genome in cancer tissues in comparison to control healthy tissues, ATXN1, PPP2R2C, CCR6, RAB37, DUSP27, ZNF521, SLC6A17, SPIN1, CXCR1, SPTBN1, NBAS, NRG3, COL5A1, CDX1, and BATF3 are mostly involved in transcriptional and immune regulation. Among this group of genes, aberrantly methylated in other human cancers were CCR6 in oral cancer(49) and chronic lymphocytic leukemia (50), RAB37 in lung cancer (51), ZNF521 in breast cancer(52), and CDX1 in gastric cancer(53), esophageal SCC (54) and in colon cancer(55). The genes involved in immune regulation could belong to the tumor-in ltrating immune cells or tumor-in ltrating lymphocytes, which are often associated with better clinical outcomes.…”
mentioning
confidence: 99%
“…The genes involved in immune regulation could belong to the tumor-in ltrating immune cells or tumor-in ltrating lymphocytes, which are often associated with better clinical outcomes. Thus, the aberrantly methylated gene CCR6 (C-C Motif Chemokine Receptor 6), which regulates the migration and recruitment of dendritic and T cells during in ammatory and immunological responses, was also found in human OSCC(49). Lee et al(49) concluded that hypomethylation of this gene may play an important role in the recruitment or retention of CCR6 + Treg cells into OSCC in ammatory microenvironment at the early stage of tumor progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation